2017
DOI: 10.1002/jbio.201600310
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear optoacoustic readings from diffusive media at near‐infrared wavelengths

Abstract: Optoacoustic (photoacoustic) imaging assumes that the detected signal varies linearly with laser energy. However, nonlinear intensity responses as a function of light fluence have been suggested in optoacoustic microscopy, that is, within the first millimeter of tissue. In this study, we explore the presence of nonlinearity deeper in tissue (~4 mm), as it relates to optoacoustic mesoscopy, and investigate the fluence required to delineate a switch from linear to nonlinear behavior. Optoacoustic signal nonlinea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Although nonlinear RSA materials are anticipated to be the most promising dye category for generation of an enhanced nonlinear PA response it must be kept in mind that their application is very much limited to scenarios where the application of high laser fluences is feasible. While a number of studies addressing nonlinear PAI have emerged very few have involved in vivo studies , none of which have relied solely on a molecular‐based contrast agent. As such, all of the in vivo imaging applications of MPACs discussed in this review have been conducted under low laser fluence conditions where the dye either behaves as a LA or SA material.…”
Section: Classes Of Photoacoustic Contrast Agentsmentioning
confidence: 99%
“…Although nonlinear RSA materials are anticipated to be the most promising dye category for generation of an enhanced nonlinear PA response it must be kept in mind that their application is very much limited to scenarios where the application of high laser fluences is feasible. While a number of studies addressing nonlinear PAI have emerged very few have involved in vivo studies , none of which have relied solely on a molecular‐based contrast agent. As such, all of the in vivo imaging applications of MPACs discussed in this review have been conducted under low laser fluence conditions where the dye either behaves as a LA or SA material.…”
Section: Classes Of Photoacoustic Contrast Agentsmentioning
confidence: 99%
“…The total exposure of the sample for simultaneous illumination with all four wavelengths is calculated to be 19.8 µJ/cm 2 per pulse and 3.96 W/cm 2 mean exposure, well below the MPE limits of 20 mJ/cm 2 and 18 W/cm 2 , imposed by the American National Standards Institute 37 . It has been demonstrated that non-linear effects in OA are present at high energy densities above ~7 mJ/cm 2 38 . The total sample exposure herein was less than 20 µJ/cm 2 , even in the case of simultaneous illumination with all wavelengths.…”
Section: Methodsmentioning
confidence: 99%
“…This might be because of the fact that at a higher concentration of the ink, any fresh addition in the number of ink species does not necessarily create a proportional increase in light absorption, thereby limiting the magnitude of the acoustic pressure, making the peak received voltage to saturate. Alternatively, it might also be due to nonlinear effects due to saturation of absorption coefficient or usage of large fluence values 38,39 . The observations obtained from Fig.…”
Section: Concentration Detection Using the Pmutmentioning
confidence: 99%